Potential of science to address the hunger issue: Ecology, biotechnology, cattle breeding and the large pantry of the sea - José Tena Medialdea; Jesús A. Prieto Ruiz; Carmen Fagoaga García; Antonio Calvo Capilla; Jerónimo Chirivella Martorell; Joel Bueso Rodenas (Journal of Innovation & Knowledge (JIK), 2018)
The knowledge about the real possibilities that current science gives us is basic to support everything that is not negative either for men or for our environment. In this way, it is an advantage to win this battle against hunger with rational use of science advantages. In this paper, we start from the basis that the solution to the problems of hunger requires the multidisciplinary action of sciences and knowledge. We provide a reflection on the possibilities to be considered from disciplines such as ecology, biotechnology, veterinary and aquaculture. The need for ecological studies where the role of human beings as part of ecosystems is considered. In addition, advances in molecular biology and precision agriculture are analyzed, evaluating their advantages and associated problems, as well as understanding the role of veterinary science and animal genetic improvement in the problem of hunger. Finally, the bases the sustainable use of sea products and expectations generated by marine crops are presented.
Keywords: Q01; Q1; Q22; 650; Hunger; Ecology; Biotechnology; Veterinary; Aquaculture